The Effect Of Service Quality, Brand Experience, Price, Trust, And Convenience Toward Customer Satisfaction And Its Effect To Positive Wom Of Bridestory Indonesia - Tannia Meyana; Margaretha Pink Berlianto (Cakrawala Repositori IMWI, 2023)
This study aims to examine the influence and effectiveness of digital marketing dimensions in producing Positive Word of Mouth as the key to brand development in the digital realm. These digital marketing dimensions are Service Quality, Brand Experience, Price Perception, Customer Trust, and Online Convenience, as well as Customer Satisfaction as a mediating variable. The research was conducted using quantitative methods with 206 respondents using Partial Least Square and Structural Equation Modeling (PLS-SEM). This study shows that the Customer Satisfaction variable which is examined through questionnaires and hypothesis testing using SmartPLS-SEM, has a direct influence on Positive WOM. Customer satisfaction itself is also heavily influenced by Service Quality, Brand Experience, Perceived Price, Customer Trust, and Convenience.